A comparison of foot pain and dynamic stability among heeled and flat foot wear users in undergraduate female medical students - Tahir, Amal; Aziz, Rida; Raza, Asim; Perveen, Wajida (Journal of the Foot & Ankle, 2025)
Objective: To compare foot pain and dynamic stability among flat and heeled footwear users in undergraduate medical students, raising awareness about the importance of appropriate footwear for improving health and stability. Methods: This analytical cross sectional study targeted 305 undergraduate female medical students to assess foot pain and dynamic stability. Participants were selected using a convenience sampling technique and pre-specified inclusion/exclusion criteria. Foot pain was measured using a 100 mm visual analog scale, with validity (0.76 to 0.84) and reliability (0.66 to 0.77). Dynamic stability was assessed using the four square step test (FSST), which showed excellent test-retest reliability (ICC = 0.92). The sample size was calculated using Yamane’s formula, resulting in 305 participants. Results: The study showed that 68.9% of participants had a normal body mass index, with 33.8% reporting no foot pain, while 56.1% experienced mild pain, and 10.2% severe pain. The ANOVA test revealed a significant increase in stability test times with higher heels (flat: 6.62s, low: 7.39s, high: 8.91s, F = 68.880, p < 0.001), and the Kruskal-Wallis test (Non normally distributed data) showed increased pain with higher heels (p = 0.001). The most common pain areas were the heels (38%) and the arch (27.9%), highlighting the negative impact of heel height on both pain and dynamic stability. Conclusion: The study indicates that elevated heel heights substantially exacerbate foot discomfort and hinder dynamic balance when compared to flat shoes among female undergraduate medical students. Level of evidence III; Analytical Cross-sectional Study.